Management strategies and valorization for waste sludge from active treatment of extremely metal-polluted acid mine drainage: A contribution for sustainable mining. (10th January 2017) - Macías, Francisco; Pérez-López, Rafael; Caraballo, Manuel A.; Cánovas, Carlos R.; Nieto, José Miguel
Abstract: This study assesses the environmental impact and the potential valorization of metal-sludge waste generated by the active neutralization of extremely metal-polluted acid mine drainage (AMD). To this end, two regulated leaching tests (EN 12457-2 and 1311 USEPA TCLP), a standardized sequential extraction protocol (BCR sequential extraction) and single leaching tests were performed using dilute common industrial acids. The results of the two standardized leaching tests showed a complete discrepancy, classifying the waste as both inert (according to the TCLP) and not suitable for disposal at landfills for hazardous waste (according to EN 12457-2). In this regard, the environmental characterization of the waste using the BCR sequential extraction lined up with interpretations made by the EN 12457-2 leaching test, reinforcing the hazardousness of this type of residue. This waste requires careful management, as evidenced by the release of high concentrations of metals (e.g., Cd, Zn, Al) when interaction with rainfall and organic acids take place, exceeding the risk threshold values for aquatic life. The easy extraction of base, industrial- and tech-metals that is possible with dilute acids encourages the consideration of this type of sludge as an interesting alternative metal source with great economic potential. The joint application of remediation treatments and metal recovery schemes could contribute to the goal of zero waste production in mining activities, which would help to develop sustainable mining practices worldwide. Graphical abstract: Image 1 Highlights: Chemical stability of sludge from extreme polluted AMD neutralization is assessed. Severe discrepancies in well-established international regulatory tests were observed. Metal release from the sludge is strongly controlled by environmental conditions. High concentrations and readily extraction of metals pose the waste as metal ore.